The relationship between perceived stress and job burnout of police officers during the COVID-19 pandemic: the mediating role of social support, sleep quality and resilience - Xuyu Chen; Yi Xu; Qi Zhang; Hongwei Huang; Xiaodong Tan; Yang Yang (BMC Public Health)
Abstract Background With the rapid spread of Corona Virus Disease 2019 (COVID-19) in China, police officers were undergoing higher job stress, which made them physically and mentally exhausted, eventually leading to job burnout. The research aims to explore the mediating role of social support, psychological resilience, and sleep quality in the relationship between perceived stress and burnout. Methods Data collection was based on multistage cluster random sampling of police in Wuhan, China, from June 2021 to October 2022. A self-administered questionnaire was adopted. Perceived stress, social support, resilience, sleep quality and job burnout were measured using international standard scales. Spearman correlation analysis was utilized to explore the correlation between various psychological conditions and job burnout. Cronbach’s α coefficient methods and confirmatory factor analysis (CFA) were applied to check the scales’ reliability and discriminant validity. The structural equation model (SEM) was performed to adjust the model fitting. Results 2125 eligible participants were included. The job burnout score was 1.90, and 8.52% showed severe burnout. The Cronbach’s α coefficients of the above scales were all ≥ 0.8. The goodness of fit test for the first-order and second-order models reached all fit indices standards in CFA. Police’s burnout and its dimensions were correlated with sleep quality, perceived stress, and social support, except between burnout, emotional exhaustion, depersonalization, and resilience. Parallel multiple mediations showed that social support, sleep quality, and resilience mediated the relationships between perceived stress and job burnout. The mediating effect of the three factors accounted for 6.72%, 55.39%, and − 7.14% of the total effect, respectively. Conclusions Perceived stress affects burnout through mediating variables such as social support, sleep quality, and resilience. The mediating effect of sleep quality is the most potent.